2022
DOI: 10.1155/2022/5501476
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Landscape of Prognostic Significance and Immune Characteristics of Myosins in Squamous Cell Carcinoma of the Head and Neck

Abstract: Myosin superfamily, a large and diverse family of molecular motors important for cell motility and migration, has been illustrated to play contradictory roles during the development of several kinds of tumors. However, the function and prognostic values of MYOs in head and neck squamous cell carcinoma (HNSCC) still remain largely unknown. In the current manuscript, the expression levels and clinical data of MYOs in HNSCC were investigated by online databases, including Oncomine, GEPIA, GEO, TCGA, HPA, UALCAN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…For instance, MYO1B in HNC promoted tumor development by mediating the process of EMT. 42 Hence, the knockdown of MYO1B attenuated the migration and invasion abilities of HNC cells, and thus significantly inhibited LNM. 43 In colon cancer, upregulation of MYO1B promoted tumor metastasis by mediating the RhoA/ ROCK/FAK signaling pathway, resulting in poor prognosis in patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, MYO1B in HNC promoted tumor development by mediating the process of EMT. 42 Hence, the knockdown of MYO1B attenuated the migration and invasion abilities of HNC cells, and thus significantly inhibited LNM. 43 In colon cancer, upregulation of MYO1B promoted tumor metastasis by mediating the RhoA/ ROCK/FAK signaling pathway, resulting in poor prognosis in patients.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that MYO1B is aberrantly expressed in a variety of tumors and is closely associated with tumorigenesis, progression, and prognosis determination. For instance, MYO1B in HNC promoted tumor development by mediating the process of EMT 42 . Hence, the knockdown of MYO1B attenuated the migration and invasion abilities of HNC cells, and thus significantly inhibited LNM 43 .…”
Section: Discussionmentioning
confidence: 98%
“…It is proposed that MYO1B may facilitated the propagation and metastasis of HNSC through the EMT process. Meanwhile, it has been recently reported that silencing of MYO1B alleviated the EMT potential of HNSC 49 .…”
Section: Discussionmentioning
confidence: 99%